2009
DOI: 10.1007/s10616-009-9239-3
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and characterization of human osteosarcoma cell lines with different pulmonary metastatic potentials

Abstract: To develop an investigative tool for the study of human osteosarcoma (OSA), we established a human OSA cell line, namely, SOSP-9607, which exhibits a potential for spontaneous pulmonary metastasis. Subsequently, we screened two related sublines (F5M2 and F4) that have different pulmonary metastatic potentials. An in vivo orthotopic transplantation assay confirmed spontaneous pulmonary metastasis in all mice (100%) transplanted with the more aggressive OSA cells (F5M2) and a lesser degree of metastases with sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 15 publications
2
48
0
Order By: Relevance
“…The human osteosarcoma cell line SOSP-9607 was established in our laboratory as described previously (4). The cells were cultured in RPMI-1640 medium (HyClone, USA) supplemented with 10% fetal calf serum (FCS; Sijiqing Co.), 100 U/ml of penicillin G and 100 µg/ml of streptomycin, in a humidified atmosphere of 5% CO 2 at 37˚C.…”
Section: Establishment and Characterization Of A Cisplatin-resistant mentioning
confidence: 99%
See 1 more Smart Citation
“…The human osteosarcoma cell line SOSP-9607 was established in our laboratory as described previously (4). The cells were cultured in RPMI-1640 medium (HyClone, USA) supplemented with 10% fetal calf serum (FCS; Sijiqing Co.), 100 U/ml of penicillin G and 100 µg/ml of streptomycin, in a humidified atmosphere of 5% CO 2 at 37˚C.…”
Section: Establishment and Characterization Of A Cisplatin-resistant mentioning
confidence: 99%
“…The 6.5-mm Transwell insert (pore size, 8 µm; 24-well insert; Corning) was pre-coated with 40 µl BD Matrigel (1:8 dilution, BD Biosciences). The cells were inoculated on the filter at a density of 5x10 4 cells/filter and incubated with serum-free medium for 48 h. The medium with 20% fetal bovine serum was added to the lower chamber outside of the insert. The cells that invaded through the Matrigel and reached the lower surface of the filter were fixed with 95% ethanol for 30 min and then stained with 0.1% crystal violet for 10 min.…”
Section: Growth Curves and The Doubling Time (T D )mentioning
confidence: 99%
“…Although HER2 is generally ONCOLOGY REPORTS 25: 325-331, 2011 recognized as an indicator of tumor migration and poor prognosis, its role in osteosarcoma is controversial (29)(30)(31)(32)(33)(34)(35)(36)(37). In this study, we investigated the expression of HER2 in SOSP-9607-E10 cells, a previously established subculture of osteosarcoma cells with relatively high metastatic potential (38). In accordance with our previous flow cytometry results (17), RT-PCR and Western blot analysis in this study demonstrated an increased HER2 expression in SOSP-9607-E10 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Human osteosarcoma cell lines with differential metastatic potentials F5M2 and F4 were previously established. 3 Saos-2, U2OS, MG63 were purchased from ATCC. The cell lines were maintained in complete RPMI 1640 medium (Thermo Scientific, SH30809.01B) supplemented with 10% fetal calf serum (FCS) (Sijiqing Co., B21000739) at 37°C under a 5% CO 2 in air atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…The anesthesia method and orthotopic transplantation procedures were based on the method reported previously. 3 Briefly, after the mice had been anesthetized by intraperitoneal injection of ketamine (0.45 mg/mouse) and xylazine (0.45 mg/mouse), tumor cells were aspirated into a 1 ml tuberculin syringe fitted with a 27-gauge needle, and the needle was inserted through the cortex of the anterior tuberosity of the tibia with a rotating movement to minimize cortical fracture. Once the cortex was traversed, the needle was pushed 3-5 millimeter into the axis of the tibia.…”
Section: Methodsmentioning
confidence: 99%